Optimasi Produksi Tepung Porang dari Chip Porang Secara Mekanis dengan Metode Permukaan Respons - Faridah, Anni; Widjanarko, Simon Bambang; Sutrisno, Aji; Susilo, Bambang (Jurnal Teknik Industri, 2012)
Porang Tuber (Amorphophallus oncophyllus) has high Glucomanan content which is very useful in food and non food industry as well as in medical industry. The only main problem in development of porang flour is its Calcium Oxalate content that stipulates irritation (itchiness) and health disorder. Optimization study of diminution (reduction) content of Calcium Oxalate during mechanical grinding process using stamp mill and blowing fractionation. Optimization was performed by applying Response Surface Model (RSM), central composite model. Three variables i.e. weight of porang chip, grinding time and grinding speed were studied in order to study the Calcium Oxalate content as a response. Response model obtained was quadratic which was acquired at 1.3 kg porang optimum weight; grinding time 17.4â€™8â€; and grinding speed at 19,23 rpm. Optimum Calcium content has been predicted at 0.2978% which was 0.3% in actual, decrease 92,12%Â